Analysis of the Determinants of Economic Growth in G20 Countries 2012-2021 - Deni Putra Paratama (Efficient: Indonesian Journal of Development Economics, 2023)
Economic growth is one of the indicators that can be used by a country to assess and evaluate the condition of economic development within a country. This research aims to examine how government debt, foreign direct investment, foreign exchange reserves, and exports can affect economic growth and aims to determine the short-term and long-term relationship of the independent variable used to the dependent variable. The data used in this research is a type of panel data starting from 2012 to 2021 with the object of research of 19 countries in the G20 group. The analytical tool used in this research is Pooled Mean Group/Autoregressive Distributed Lag (ARDL). The results of this research show that in the short-term government debt, foreign direct investment has a positive and insignificant relationship with economic growth. On the other hand, exports have a positive and significant relationship to economic growth in the short term.